Fiber optic cable infrastructure and dispersion compensation for storage area networks. - DeCusatis, Casimer M. (IEEE Communications magazine)
The fiber optic cable infrastructure currently used by many large data centers is over 10 years old, and may soon require upgrading in order to support higher-data-rate services. Legacy multimode optical fiber is typically low bandwidth, and will only support limited distances at data rates exceeding 1 Gb/s. In this article we investigate various methods for extending the distance of multimode fiber at higher data rates. This includes the tactical use of enhanced bandwidth multimode fiber, electronic dispersion compensation, and wavelength tuning control loops.